Image, krop og maskulinitet. Mediediskurser om skihoppere - Pfister, Gertrud; Jeppesen, Rikke Schou (Forum for Idræt, 2008)
Artiklen beskriver og forklarer de forandringer, som sporten har gennemgået, og den indflydelse, som disse forandringer har haft på udøvere og på deres kroppe og images. Der er særlig fokus på mediernes rolle i forhandlingen om konstruktion af ambivalente maskulinitetsformer. Gertrud Pfister & Rikke Schou Jeppesen: Images, Bodies and Masculinities. Media discourses about Ski Jumpers Today ski jumping can be considered a typical media sport: it has very few participants and no basis to become a »sport for all« movement. Nevertheless, the few specialists and their main events attract masses of spectators and great media attention. The high demands of skill and strength as well as the danger involved have made ski jumping a typical male sport. Since its beginnings in the 19th century a ski jumper was looked upon as the epitome of »true manhood«. Today ski jumpers are celebrities with fragile egos, skinny bodies, boyish looks, ambivalent masculinities and fan communities of teenage girls. With a constructivist theoretical approach, we will describe and explain the changes that have taken place in ski jumping and the effects of these changes on the athletes, their bodies, their images and their masculinities. The focus will be on the media representation of two German ski jumpers, Martin Schmitt and Sven Hannawald who dominated this sport between 2000 and 2003. Sources are the articles about these athletes in 6 German print media. With a qualitative content analysis, we explore the media coverage of ski jumping and the way the athletes are presented. The correlations between the images and the »doing gender« of the athletes and their presentations in the media along with the role of the media in constructing new and ambivalent masculinities will be the key issues of this article.